Grey Relational Analysis for the Production of Dimethyl Ether Syngas in a Biomass Pyrolysis Reactor - Lei, Tingzhou; Wang, Zhiwei; Sun, Yanhua; Shi, Xinguang; He, Xiaofeng; Zhu, Jinling (Journal of Technology Innovations in Renewable Energy, 2013)
In this study, dimethyl ether (DME) syngas using a biomass pyrolysis reactor was produced. Gas production parameters, including pyrolysis temperature (PT), pumping frequency (PF) of the root blower, and the feeding rate (FR) of the pyrolysis chain motor, were optimised. The H2 and CO content of the biomass gas, as well as the H2:CO ratio, were examined. The relationship between gas production parameters and the biomass gas content was analysed using grey relational analysis (GRA). The result shown that PT had the greatest effect on H2 and CO content and the H2:CO ratio of the biomass gas. FR was the second most influential parameter, followed by PF. CO content was influenced most by the three parameters. The optimal DME syngas H2:CO ratio was approximately 2, and this ratio was improved using GRA, which increased the H2 and CO content as well as the H2:CO ratio during DME synthesis from biomass gas.